EDUCATIONAL ACTION RELATED TO BED POSITION AS A STRATEGY TO MINIMIZE THE RISK OF PNEUMONIA ASSOCIATED WITH MECHANICAL VENTILATION (Fiep Bulletin - online, 2013)
the relative risk of mechanical ventilation-associated pneumonia (VAP) can be related to the patient's characteristic and the preventive care used by the health team during his/her hospital stay. Among these we can cite the patient's positioning in bed. Thus, when this care is not performed, the patient is at risk of acquiring VAP due to the aspiration of gastric and oral-pharynx contents. When this failure is detected during care, some measures must be taken, both to prevent as well as to minimize the worsening of VAP. Studies prove the reduction on VAP rates when educational strategies are taken in order to change professional practice actions. OBJECTIVE: to identify whether there's a difference between care given by health professionals to patients undergoing mechanical ventilation interned in an ICU in regard to bed positioning, before and after an educational intervention. METHODOLOGY: quasi-experimental study, quantitative, time-series outlining, prospective data, in a hospital in the city of Natal, from November 2007 to march 2008, with 31 nursing professionals on three moments: systematic observation, educational intervention, considering flaws, and replication of the observation. RESULTS: we detected a young population, female, most nursing technicians, never having been through training regarding VAP prevention; as for care related to the patient's positioning in bed, before the educational interventional the decubitus change was performed on 51.3% of the occasions; afterwards on 78.2% of the occasions (p=0.0005); before: 95.5% the bed's back rest was kept elevated; afterwards: the intervention, on 98.2% of the observations, the patient's bed's back rest was kept elevated (p=0.38%). CONCLUSION: there was an improvement on the quality of care five when compared to the moment prior to the educational intervention.
Keywords: Pneumonia; Ventilator-Associated (VAP); Education; Intensive Care Units